Formulation and evaluation of oral fast dissolving film containing glibenclamide - B. Mohan; D. Karthikeyan; G. Ganesh kumar (International Journal of Pharmacy and Analytical Research, 2022)
Glibenclamide (GBC) is an oral hypoglycemic drug that stimulates the pancreatic beta cells to secrete insulin and is often used to treat diabetes, including diabetes during pregnancy. In present research work an attempt has been made to prepare mouth dissolving films of Glibenclamide (GBC) were prepared using different polymers like HPMCE5, HPMCE15 by solvent casting method. The fast dissolving oral film evaluated for folding endurance, swelling index, surface pH, in-vitro disintegration time, drug content, drug polymer compatibility (IR Study), and in-vitro drug release. The physical appearance and folding endurance properties were found to be good and electron microscopy shows that films are clear, colorless with smooth surface without any scratches. The surface pH was found to be in the range of 6.35 to 6.75 which is close to salivary pH, which indicates that films may have less potential to irritate the oral mucosa, thereby they are comfortable. The drug content of all the films was in the range of 95 to 99 suggesting that drug was uniformly dispersed throughout all films. The In-vitro disintegration time of films prepared with HPMCE5 &HPMCE15 was in the range of 25 to 35 sec. the Invitro dissolution results showing that FA8 producing 98.59% Hence it can be inferred that the fast dissolving oral film of Glibenclamide may produce the rapid action thereby improving bioavailability and enhance the absorption by avoiding the first pass effect.